Analysis of new growth promoting black market products. (August 2018) - Krug, Oliver; Thomas, Andreas; Malerød-Fjeld, Helle; Dehnes, Yvette; Laussmann, Tim; Feldmann, Ingo; Sickmann, Albert; Thevis, Mario
Abstract: Detecting agents allegedly or evidently promoting growth such as human growth hormone (GH) or growth hormone releasing peptides (GHRP) in doping controls has represented a pressing issue for sports drug testing laboratories. While GH is a recombinant protein with a molecular weight of 22 kDa, the GHRPs are short (3–6 amino acids long) peptides with GH releasing properties. The endogenously produced GH (22 kDa isoform) consists of 191 amino acids and has a monoisotopic molecular mass of 22, 124 Da. Within this study, a slightly modified form of GH was discovered consisting of 192 amino acids carrying an additional alanine at the N-terminus, leading to a monoisotopic mass of 22, 195 Da. This was confirmed by top-down and bottom-up experiments using liquid chromatography coupled to high resolution/high accuracy mass spectrometry. Additionally, three analogues of GHRPs were identified as Gly-GHRP-6, Gly-GHRP-2 and Gly-Ipamorelin, representing the corresponding GHRP extended by a N-terminal glycine residue. The structure of these peptides was characterised by means of high resolution (tandem) mass spectrometry, and for Gly-Ipamorelin and Gly-GHRP-2 their identity was additionally confirmed by custom synthesis. Further, established in-vitro experiments provided preliminary information considering the potential metabolism after administration. Highlights: Top-down and bottom-up analysis of growth promoting products In-vitro metabolism of peptides High resolution mass spectrometry Unknown black market products